(untitled) (The International Journal for Scientific Research, 2024)
This study aims to examine the impact of innovation on the efficiency of government services in Saudi Arabia and how these innovations can improve the quality of life for citizens. The study is based on the analysis of data collected from surveys and interviews with government officials and citizens, as well as a review of previous studies and scientific theories related to innovation. The results show that technological and administrative innovations significantly contribute to improving the efficiency of government services and increasing citizen satisfaction. Recommendations include enhancing community awareness of the importance of innovation, developing technological infrastructure, and encouraging collaboration between the public and private sectors.